Teachers’ Instructional Language with Children with Mild and Severe Language Difficulties in Self-contained Special Education Classrooms - Zheng, Wenjing (Journal of the American Academy of Special Education Professionals, 2023)
Teachers’ instructional language is often described as key in facilitating the learning of children with disabilities. This article explored two teachers’ instructional language as used in interactions with children with mild and severe language difficulties in one-on-one instructional sessions. The results showed that teachers used more declarative sentences to convey information with students with mild communication difficulties and more imperative sentences to express requests with students with severe communication difficulties. The language used across all students was mainly on the concrete level, with little opportunity to facilitate higher levels of cognitive activities. One teacher used longer sentences with a student with mild impairments than with a student with severe language difficulties. The most frequently used words reflected the use of core vocabulary in the classrooms. Implications and limitations of the study are discussed. [Note: The author and abstract found via the url is for another article and is incorrect.]